OPPORTUNITIES AND CHALLENGES OF COACHING AFTER THE COVID-19 PANDEMIC: EDUCATIONAL TECHNOLOGICAL TOOLS AIMED AT EDUCATIONAL COACHING - Ribeiro Rubim Fernandes, Ivete; do Carmo da Silva Campos, Manuel; Rubim Fernandes, Leticia (Revista Gênero e Interdisciplinaridade, 2023)
When we look at the world scene today, it is clear that the spread of the new coronavirus, which causes COVID-19, has led to profound changes in social, organizational and work interaction. In education it is not, and it will not be different. These new insights have begun to promote new ways of learning, teaching, work and communicate, and the coaching and tools, as well as new educational technologies as a factor of innovation and proactivity. This study aimed to: Analyze future perspectives related to post-pandemic coaching and possible emerging technological tools. The theoretical basis is based on studies at national and international level on possible scenarios involving coaching in the post-pandemic of COVID-19. The studies are recent and involve the period from December 2019 to May 2020, with a qualitative approach, with exploratory purposes having as methodological procedures the bibliographic research and the observations of the author of this study. The results show that humanity is being forced to rethink its daily life and ways of living, and this is an opportunity to be explored by the coach. We conclude that there will be a need to rethink coaching aimed at the use of new technologies, as well as the coaching work itself and the way it interacts and guides the coachee, from the perspective of post-pandemic educational coaching.